Psychological and relational adjustment under stress: the mediating role of emotion regulation in parents' functioning during the COVID-19 crisis - Taurino, Alessandro; Cassibba, Rosalinda; Semeraro, Cristina; Coppola, Gabrielle; Dentamaro, Maria; Musso, Pasquale (Frontiers in Psychology, 2025)
IntroductionPeriods of intense, prolonged stress, such as the COVID-19 pandemic, can undermine parents' psychological and relational adjustment. Guided by the Family Stress Model and transactional theory, we examined whether specific cognitive emotion-regulation strategies account for the association between pandemic stressors and parental functioning.MethodsBetween April and May 2021, 212 parents of school-aged children in Southern Italy (89.6% mothers; Mage = 42.6 years) completed an online survey that assessed perceived viral threat, pandemic-related financial hardship, COVID-19 psychological impact, five cognitive emotion-regulation strategies (positive reappraisal, putting into perspective, planning, rumination, catastrophizing), psychological wellbeing (positive affect, flourishing), and relational functioning (parent-child closeness, parent-teacher joining).ResultsStructural equation modeling with robust maximum likelihood estimation controlled for parent age, gender, direct COVID-19 exposure, and socioeconomic status. The final model demonstrated excellent fit. Perceived threat and psychological impact predicted poorer wellbeing indirectly through higher catastrophizing and, only for psychological impact, lower planning. Catastrophizing and planning fully mediated these pathways, whereas rumination and other adaptive strategies were non-significant. Financial hardship was unrelated to emotion-regulation strategies yet directly associated with poorer relational functioning.DiscussionThese findings highlight catastrophizing as a maladaptive and planning as an adaptive pathway through which pandemic stress translates into parental adjustment difficulties, informing the design of targeted coping-skills programs and economic relief policies.